2019
DOI: 10.13073/fpj-d-18-00049
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nontimber Forest Products to Rural Household Income in the Kassena-Nankana West District of Ghana

Abstract: The contribution of income from nontimber forest products (NTFPs) to rural livelihoods and household income has received global recognition. However, there are growing concerns of overexploitation of NTFPs driven by poverty and policy neglect that threaten the sustainability of the NTFP resource base in Kassena-Nankana West District (KNWD) of Ghana. The study investigated the contribution of income from NTFPs to household income and socioeconomic factors that influence the collection and marketing of NTFPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…This implies that people with larger household sizes were compelled to participate in rosehip harvesting more than those with fewer members because they have more people to feed. This nding backs up previous research that found a positive and signi cant relationship between household size and forest resources dependency (Aung et al, 2014;Adongo et al, 2019). According to Suleiman et al (2017), large families have limited land holdings and high food dependency ratios, so they rely on natural resource collection due to the availability of family labour.…”
Section: In Uencing Individual's Decisions To Participate In Rosehip ...supporting
confidence: 72%
See 2 more Smart Citations
“…This implies that people with larger household sizes were compelled to participate in rosehip harvesting more than those with fewer members because they have more people to feed. This nding backs up previous research that found a positive and signi cant relationship between household size and forest resources dependency (Aung et al, 2014;Adongo et al, 2019). According to Suleiman et al (2017), large families have limited land holdings and high food dependency ratios, so they rely on natural resource collection due to the availability of family labour.…”
Section: In Uencing Individual's Decisions To Participate In Rosehip ...supporting
confidence: 72%
“…Consistent with prior expectations, the negative correlation of gender with the individual's decision to participate in rosehip harvesting suggests that women headed households relied more on rosehip harvesting because they are likely to have larger households, are often poorer and thus greater demands on them. According to Adongo et al (2019), most men do not participate in harvesting because it is assumed that collecting forest products is the responsibility of women. In this study, out of 80 respondents involved in rosehip harvesting, 69 were female.…”
Section: In Uencing Individual's Decisions To Participate In Rosehip ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut Irawanti et al, (2012), penanaman jenis HHBK sangat membantu dalam memperoleh pendapatan usahatani hutan rakyat yang berkesinambungan. Studi Adongo et al, (2019) menegaskan pendapatan HHBK cukup besar bagi masyarakat pedesaan di tanah komunal Afrika Selatan dan secara konsisten melebihi pendapatan gabungan pertanian dan peternakan yang subur. Hasil kajian Nugroho et al (2015) juga menyebutkan bahwa HHBK memiliki kontribusi sebesar 25,16% terhadap pendapatan petani di Desa Bukabuka, Sulawesi Utara.…”
Section: Pendahuluanunclassified
“…Sub-Sahara Africa hosts about 15% of the total global forest cover, with over 80% of its population depending on the forest for their livelihoods (Adongo et al 2019, FAO 2020. This sub-region is not spared from the grievous impact of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%